2‐Phenoxyethanol – Method for the determination of 2‐phenoxyethanol in workplace air using gas chromatography after thermal desorption [Air Monitoring Methods, 2018]. Issue 3 (25th July 2019) - Tschickardt, M.; Krämer, W.; Schmitt, R.; Hebisch, R.; Hartwig, A.; ,
Abstract: This analytical method is a validated measurement procedure for the determination of 2‐phenoxyethanol [122‐99‐6 ] in workplace air in a concentration range of one tenth up to twice the currently valid MAK value of 5, 7 mg/m 3 . With this method simultaneously airborne 2‐phenoxyethanol in the gaseous state as well as particles are collected. Sampling is performed by drawing a defined volume of air through a quartz fibre filter located in the sampling head with an adsorption tube filled with Tenax TA® connected downstream using a suitable pump. The flow rate is set to 0.066 L/min with a recommended air sample volume of approx. 4 litres. The collected 2‐phenoxyethanol alcohol is thermally desorbed and then analysed by means of gas chromatography using two detectors, a FID for quantification and a MSD to recognise potential interferences. The quantitative determination is based on a calibration function obtained by means of a multi‐point calibration. The limit of quantification is 0, 095 mg/m 3 based on an air sample of approx. 4 litres.